Litt's drug eruption & reaction manual - Shear, Neil H. (Milton : CRC Press LLC, 2020)
Internationally relied upon by medical practitioners for its unparalleled focus on adverse effects and cutaneous reactions, Litt's Drug Eruption & Reaction Manual is a succinct clinical reference and essential drug-safety tool for patient care. This 26th edition has been comprehensively revised and updated throughout to act as a quick reference, and each entry includes:* Summaries of numbers of reports and incidence for reactions* Clinically important and potentially hazardous drug-drug interactions* Categories of adverse drug reactions, eruptions, and cutaneous reaction patterns* Essential reference information on prescription and over-the-counter drugs as well as biologics and supplements The book contains... * A to Z listing of the 1500 most consulted generic drug and herbal drug profiles, including generic and trade names; pharmaceutical company; indications; half-life; interactions; pregnancy category; and categories of adverse reactions/eruptions, with summaries of number of reports or level of incidence of reaction* Over 31,000 adverse reactions and drug-eruption listings * Supplements, vaccines, and other biologics* Descriptions of important reactions* List of drugs that cause important reactions* List of main classes of drugs as a quick clinical reference guide* 26 tables showing the reaction profile for members of a class of drugs (such as ACE inhibitors or statins), enabling a clinician to see at a glance whether a reaction is common to all drugs included in that class, or to a majority of them, or is known in only a handful--this information can be used as the basis for an informed decision to change drugs inside the same class* 2 tables showing reported genetic associations with cutaneous adverse drug reactions and recommendations regarding genetic screening to prevent cutaneous adverse drug reactions* A concordance of synonyms and trade names for ease of cross-reference
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: MEDICAL / General; MEDICAL / Dermatology; MEDICAL / Family & General Practice; Drugs -- Side effects; Drug-exanthems.; Dermatotoxicology